THE EFFECT OF TEAMS GAMES TOURNAMENT (TGT) LEARNING MODEL WITH MONOPOLY GAME MEDIA ON MATHEMATICS LOGIC INTELLIGENCE - Pangesti, Nia; Mardiana, Tria; Rasidi, Rasidi (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of of Teams Games Tournament (TGT)learning model with monopoly game media on mathematical logic intelligence in grade VStudent of SD Negeri Keji 2, Muntilan District, Muntilan Regency.This type of research is pre-experimental with one group pretest-posttest design.The sample taken in class V SD Negeri Keji 2 with a total of 18 students.The sampling technique used was saturated sampling. Test data analysis usingprerequisite test or normality test and hypothesis testing. Data retrieval through multiplechoice test questions was then analyzed using the Wilcoxon test in the SPSS 23.00 programfor windows.The results showed that the Teams Games Tournamnet learning model withmonopoly game media had an effect on students mathematical logis intelligence. This isevidenced by the results of the analysis of the Wilcoxon signed rank test analysis of-3.732with Asymp. Sig 2 tailed is 0,000 < 0,005. So that Z output < mean rank or 3,732 < 9,50 Hais accepted and Ho is rejected. The data identify the data points are smaller than theaverage. Based on the result of the analysis the and discussion, there are differences inthe in the results of the average value, namely the initial measurement (pretest) of 41,3and the final measurement (posttest) of 73,1. From the results of the study it can beconcluded that the Teams Games Tournament (TGT) learning model with monopoly gamemedia has an effect on students mathematical logic intelligence.